[PP.02.16] TWO-YEAR FOLLOW-UP OF MEN WITH ARTERIAL HYPERTENSION TREATED WITH LISINOPRIL AND HYDROCHLOROTHIAZIDE. (September 2017) - Stojanov, V.; Radivojevic, N.; Paunovic, K.; Jakovljevic, B.
Abstract : Objective: The aim was to assess the effects of two-year antihypertensive therapy with lisinopril and hydrochlorothiazide on blood pressure of hypertensive men. Design and method: The study was designed a two-year prospective survey of persons with arterial hypertension treated with a fixed combination of 20 mg lisinopril and 12.5 mg hydrochlorothiazide. In total, 59 persons with newly-diagnosed arterial hypertension, aged from 30 to 80 years, were enrolled in the study. All patients were invited for control examinations two months, six months, 12 months and 24 months after the initiation of antihypertensive therapy. Blood pressure (BP) was measured by an oscillometric device at the beginning of the study, and at all control examinations. The differences from baseline values were tested with Student's t-test for paired samples. Results: Mean systolic blood pressure (SBP) for all men at the beginning of the study was 163.47 ± 7.73 mmHg; mean diastolic blood pressure (DBP) was 96.83 ± 6.12 mmHg. During the therapy, SBP decreased significantly by 27.37 ± 11.68 mmHg after 2 months, by 36.61 ± 13.47 mmHg after 6 months, by 39.75 ± 8.93 mmHg after 12 months, and by 34.66 ± 13.42 mmHg after 24 months, in comparison to the baseline values. DBP decreased by 20.39 ± 9.57 mmHg after 2 months, by 29.63 ± 12.15 mmHg after 6 months, by 29.97 ± 10.60 mmHg after 12 months, and by 23.19 ± 10.99 after 24 months, in comparison to the baseline values. Systolic and diastolic blood pressures after 24 months of therapy were somewhat higher than those after 12 months of therapy. Conclusions: Fixed combined antihypertensive therapy with lisinopril and hydrochlorothiazide is effective in hypertensive men from two months to two years of therapy.